A Review on Compressed Sensing Space-Time Frequency Index Modulation in OFDM System (International Journal of Innovative Research in Computer Science & Technology, 2019)
In wireless communication, orthogonal  frequency division multiplexing (OFDM) plays a major role because of its high transmission rate. In  space-time shift keying (STSK), the information is  conveyed by both the spatial and time dimensions,  which can be used to strike a trade-off between the  diversity and multiplexing gains. On the other hand,  orthogonal frequency division multiplexing (OFDM)  relying on index modulation (IM) conveys information  not only by the conventional signal constellations as in  classical OFDM, but also by the indices of the  subcarriers. In this review compressed sensing (CS) is  studied in order to increase throughput and bit-error  performance by transmitting extra information bits in  each subcarrier block as well as to decrease the  complexity of the detector.
Keywords: OFDM, MIMO; Space-Time Shift Keying (STSK); Frequency Index Modulation; Compressed Sensing (CS)